Effects of melatonin on airway inflammation in experimental models of asthma, COPD and the asthma-COPD overlap - Scheffer, Vitorio Crema; Ribeiro, Cristiane; Camargo, Leandro; Leick, Edna Aparecida; Tibério, Iolanda de Fátima Lopes Calvo (Revista de Medicina, 2023)
Background and Objectives: According to previous studies, melatonin, an indolamine, may possibly reduce dyspnea in patients with asthma or COPD. Additionally, it has also been proven, through experimental studies, that the molecule possibly plays an anti-inflammatory role, because it might inhibit transcription of NFk-B in experimental models of asthma and COPD. This study aims to investigate the effects of melatonin in experimental models of asthma, COPD and Asthma-COPD Overlap (OCP). Methods: 64 mice were divided into 8 groups in order to induce COPD (group “ALS”), asthma (“OVA”) or OC (“ACO”). The control group (“SAL”) received saline. The treatment groups (“+MEL”) were submitted to both disease protocols and also received Melatonin (intraperitoneally). After the protocols, the exhaled nitric oxide (Eno) and the total and differential cells of the bronchoalveolar lavage fluid were evaluated. Results: OVA+MEL (11.3±1.65ppb) showed reduction in Eno compared to OVA (24.17±4.30ppb). In the analysis of the bronchoalveolar lavage fluid cells, OVA+MEL (11.3±1.65x104 cells/mL) and ACO+MEL (2.17±0.63x104 cells/mL) showed a reduction in the amount of total cells compared to OVA (25.70±4.59x104 cells/mL) and ACO (14.33±3.11x104 cells/mL), respectively. There was a decrease in eosinophil count in OVA+MEL (5.37±1.41x104 cells/mL) and ACO+MEL (0.87±0.36x104 cells/mL) compared to OVA (18.67±4.01x104 cells/mL) and ACO (1.45±0.41x104 cells/mL), respectively. Additionally, the number of lymphocytes decreased in OVA + MEL (1.00±0.24x104 céls./mL) compared to OVA (3.94±1.15x104 cells/mL). The number of macrophages also decreased in OVA + MEL (3.09±0.39x104 cells/mL) and ACO + MEL (1.10±0.27x104 cells/mL) compared to OVA (7.26±1.93x104 cells/mL) and ACO (6.41±1.54x104 cells/mL), respectively. There was no difference in the comparison of neutrophil counts in the different groups analyzed.